STREAMLINING FINANCIAL PROCESSES IN PUBLIC PROCUREMENT: THE EXAMPLE OF UZBEKISTAN’S METALLURGICAL COMBINE (European Journal of Economics, Finance and Business Development, 2024)
This article explores the enhancement of financial processes within public procurement, focusing on the Metallurgical Combine of Uzbekistan as a case study. The research aims to identify inefficiencies in the existing financial mechanisms and propose strategies to streamline procurement activities. Through a detailed analysis of the Metallurgical Combine’s procurement system, the study highlights the key challenges and opportunities for improvement. Key recommendations include adopting advanced financial management software, improving transparency in financial transactions, and enhancing regulatory compliance. The findings demonstrate that by optimizing financial processes, the Metallurgical Combine can achieve significant cost savings, improved procurement efficiency, and better resource allocation. This case study offers valuable insights for other public sector entities aiming to refine their procurement financial mechanisms and achieve similar benefits.